2017
DOI: 10.3390/toxins10010022
|View full text |Cite
|
Sign up to set email alerts
|

A Single Neonatal Exposure to BMAA in a Rat Model Produces Neuropathology Consistent with Neurodegenerative Diseases

Abstract: Although cyanobacterial β-N-methylamino-l-alanine (BMAA) has been implicated in the development of Alzheimer’s Disease (AD), Parkinson’s Disease (PD) and Amyotrophic Lateral Sclerosis (ALS), no BMAA animal model has reproduced all the neuropathology typically associated with these neurodegenerative diseases. We present here a neonatal BMAA model that causes β-amyloid deposition, neurofibrillary tangles of hyper-phosphorylated tau, TDP-43 inclusions, Lewy bodies, microbleeds and microgliosis as well as severe n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 137 publications
0
9
0
Order By: Relevance
“…These caveats notwithstanding, we feel the weight of available evidence bears strongly against an anti-herbivore function of BMAA, based both on the absence of short-term effects in the current study and on the extensive latency between exposure and the onset of toxic effects observed in other animals 28 . In mammals, for example, BMAA exposure at a young age can cause neurological symptoms that become apparent only much later in life 11 , 39 . Similarly, fruit fly larvae reared on BMAA-laced diet exhibited delayed locomotive impairment as adults, even though BMAA did not negatively affect larval survival 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These caveats notwithstanding, we feel the weight of available evidence bears strongly against an anti-herbivore function of BMAA, based both on the absence of short-term effects in the current study and on the extensive latency between exposure and the onset of toxic effects observed in other animals 28 . In mammals, for example, BMAA exposure at a young age can cause neurological symptoms that become apparent only much later in life 11 , 39 . Similarly, fruit fly larvae reared on BMAA-laced diet exhibited delayed locomotive impairment as adults, even though BMAA did not negatively affect larval survival 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, the biological and ecological functions of BMAA for cycads remain uncertain: although some metabolic and signaling functions have been proposed, the most prevalent hypothesis for an adaptive function of BMAA in cycads is that it confers protection against herbivory, consistent with its demonstrated toxicity to diverse organisms including non-human primates and other mammals 9 11 , crustaceans 3 , fish 12 , and microbes 13 . Indeed, numerous papers implicitly or explicitly refer to BMAA as an anti-herbivore compound 14 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although more studies are needed, recently Martin and colleagues showed a relation between BMAA and microcystin leucine and arginine (other cyanotoxins) with the neurodegeneration, using a larval zebrafish model [ 42 ]. In addition, new-born rats exposed to BMAA were affected by motor defects, suggesting that exposure during neural development could lead to develop ALS [ 43 ]. Previous studies investigated the mechanisms of action of BMAA on the neurodegeneration: BMAA kills NADPH-diaphorase-positive motor neurons and plays a toxic role to glial cells affecting motor neuron injury [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vitamin D has been proposed as a potential treatment to delay ALS although a definitive answer with regard to its effectiveness is yet to be reached (Libonati et al, 2017). Another example is represented by pioglitazone, a compound that protected against neurodegeneration in SOD1 G93A transgenic mice (Schutz et al, 2005) but was eventually found ineffective in a double blind, placebo controlled study as add-on therapy with riluzole in ALS patients (Dupuis et al, 2012). The observation that some of these molecules can affect TDP-43 functions might therefore represent an opportunity to re-evaluate their usefulness in the fight against ALS.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%